Clinical diagnosis and treatment of seven patients diagnosed pneumonia caused by Chlamydia abortus: a case series report - Wen, Ya; Du, Yanjia; Shi, Xiaoyan; Zeng, Zixiong (Frontiers in Medicine, 2024)
Background Chlamydia abortus pneumonia is very rare in normal people. At present, there is a lack of clinical data on the clinical characteristics and diagnosis and treatment experience of patients with this type of infection. Our team had recently treated 7 cases of these patients. This study aims to comprehensively summarize and analyze the clinical characteristics and treatment methods of Chlamydia abortus pneumonia, and to provide clinical evidence for the diagnosis and treatment of Chlamydia abortus pneumonia. Methods Clinical data were retrospectively collected from patients diagnosed with Chlamydia abortus pneumonia through metagenomic next-generation sequencing (mNGS) at the Department of Pulmonary and Critical Care Medicine, Meizhou People’s Hospital. Results Seven patients with Chlamydia abortus pneumonia reported a history of poultry exposure, experiencing fever alongside respiratory or digestive symptoms. Marked elevation of blood inflammation markers, accompanied by hypoproteinemia and liver damage, was observed. Chest CT scans revealed pneumonia and pleural effusion. Chlamydia abortus was detected in blood or bronchoalveolar lavage fluid (BALF) through mNGS, often co-occurring with Chlamydia psittaci or other bacteria infections. Notably, Doxycycline demonstrated efficacy in treating Chlamydia abortus. Conclusion Chlamydia abortus infection is a zoonotic disease, particularly among individuals with a history of poultry exposure, and mNGS emerges as a reliable diagnostic tool for its detection. Chlamydia abortus infection manifests with systemic and lung inflammation, effectively addressed through Doxycycline therapy.